IMPACT OF TRANSFORMATIONAL LEADERSHIP ON TEACHER’S TECHNO-PEDAGOGICAL COMPETENCE: THE MEDIATING ROLE OF MOTIVATION - Astuti, Ruli; Abidin, Munirul (PT. Antis International Publisher, 2024)
Objective: This study investigates the impact of transformational leadership on teacher’s performance in integrating technology into teaching (techno-pedagogy), with motivation as a mediating role. The objective of this study is examining the direct influence of transformational leadership on teacher performance, the role of motivation as a mediator, and the relationship between teacher performance and technology integration. Method: A quantitative approach was used in this research. The population were 137 teachers from several schools in East Java, with 104 randomly selected as samples. The SmartPLS 4 program was used for analysis, which included validity and reliability testing as well as the relationship between variables. Results: The findings show that transformational leadership significantly enhances teacher motivation, which improves their performance in integrating technology. However, transformational leadership does not directly influence teacher performance. Instead, motivation serves as a full mediator, connecting leadership and teacher effectiveness. Novelty: This study emphasizes the crucial role of motivation in enhancing techno-pedagogical practices and provides insights into the necessity of transformational leadership that prioritize teacher support, motivation, and providing resources in order to improve educational outcomes.